Analisis Perkembangan Return On Asset (ROA) Dan Return On Equity (ROE) Untuk Mengukur Kinerja Keuangan Pada PT. Industri Jamu Dan Farmasi Sidomuncul, Tbk. - Amin Rahmatullah; Nurhayati Nurhayati; Aris Munandar (Sharing: Journal of Islamic Economics Management and Business, 2025)
The purpose of this study is to examine how well Return on Assets (ROA) measures the financial performance of PT Industri Jamu dan Farmasi Sidomuncul, Tbk, and how well Return on Equity (ROE) measures the company’s financial performance. The data analysis technique employed in this study is a quantitative method, involving relevant calculations related to the research problem. Descriptive analysis is conducted on the Return on Assets (ROA) and Return on Equity (ROE) ratios, which are then interpreted by comparing them with the industry average standards for ROA and ROE. In addition, this study applies statistical analysis using a one-sample t-test with the assistance of SPSS version 22. Based on the results and discussion, it can be concluded that the Return on Assets (ROA) used to measure the financial performance of PT Industri Jamu dan Farmasi Sidomuncul, Tbk is greater than or equal to 5.98%, which meets the expected standard and is considered good. Likewise, the Return on Equity (ROE) used to measure the company’s financial performance is greater than or equal to 8.32%, which also meets the expected standard and is considered good.